Sanggar Andhika Jaya dalam Pelestarian Tari Kiprah Glipang di Desa Pendil, Kecamatan Banyuanyar, Kabupaten Probolinggo Tahun 1980-2024 - Putri, Mia Widasari Kiswari; Ida Ayu Wirasmini Sidemen; Anak Agung Inten Asmariati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the role and forms of preservation of the Kiprah Glipang Dance carried out by the Andhika Jaya Studio in Pendil Village, Probolinggo Regency, from 1980 to 2024. This research uses a qualitative method with a historical approach. Data collection techniques were carried out through observation, in-depth interviews with key informants, and document studies. The results show that Sanggar Andhika Jaya carries out comprehensive preservation through three main forms: (1) structured regular training with age grouping and a dancer regeneration system, despite facing challenges such as student discipline and the lack of regeneration for singers and musicians; (2) active participation in various art festivals from local to national levels, which functions as cultural promotion and education; and (3) contribution to government policy that establishes the Kiprah Glipang Dance as a local content subject in schools. The studio's existence also has positive implications for the community, such as strengthening social bonds and boosting the local MSME economy, and for the local government as a strategic partner in preserving cultural heritage and building the region's image. It is concluded that Sanggar Andhika Jaya has not only succeeded in maintaining the authenticity of the dance but has also innovated it into a therapeutic and cultural promotion medium.